HUBUNGAN ANTARA STRES BELAJAR TERHADAP PERILAKU PRODUKTIF SANTRI DI PONDOK PESANTREN MAHASANTRI MIFTAHUL KHOIR DAGO BANDUNG - Wahyudi, Mustadim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
Maintaining and improving the quality and quantity of services provided by Islamic education service institutions requires results demonstrated by students. It is not an easy task to keep students behaving constructively. Learning stress is one factor that is often associated with this characteristic. The aims of the Research was to see the relationship between the productive behavior of students of Pondok Pesantren Mahasantri Miftahul Khoir Dago Bandung and the level of learning stress. The study findings show that the rxy magnitude is - 0.204 < r table 5% is 0.279, which indicates that the hypothesis is rejected which states that there is a relationship between learning stress and productive behavior of students at a significant level of 5%. With such, it is impossible to anticipate the level of productivity of students based on the level of stress they experience in learning.